33Application of Gaussian Wave Functions for 1s States in Helium and Helium Like Atoms - Mahmood, Maysoon A; Adil, Ban Hassan; Al Bayati, Khalil H (Al-Nahrain Journal of Science, 2013)
Properties of Gaussian like orbital wave function and Slater like orbital wave function for Helium atom and Helium like ions was studied. This included energy, the radial distribution function, the shape of the wave function near the nucleus and the orbital exponent. For Gaussian the values of the orbital exponent and the constants varied using linear combination of four Gaussian functions to approximate the radial component of atomic orbital, the obtained result is better than universal result.